At the roots of Plant Awareness Disparity (PAD): Semantic processing and numerosity perception - Silvia Guerra; Marco Roccato; Carolina Maria Oletto; Andrea Ghiani; Marco Bertamini; Luca Battaglini (PLoS ONE, 2026)
Plant Awareness Disparity (PAD) refers to the inability of humans to notice plants and recognize their importance. Among the various factors (e.g., cultural) contributing to PAD, the less prominent visual cues of plants (e.g., color) might be one of the main features making them less noticeable to human perception. Here, we investigated whether PAD affects basic numerosity perception, which represents a fundamental cognitive ability that allows individuals to interpret and interact with their surroundings. Across three experiments, we compared how participants perceive the numerosity of plants (specifically trees), animals, and minerals. Participants completed two tasks: an estimation task, in which they reported the exact number of items in a single set and a comparison task, which required them to discriminate numerosity between two sets of items. In Experiment 1, both tasks employed colored images. We hypothesized that participants would underestimate the number of plant items in comparison to animals and minerals, given that plant stimuli typically attract less attention. In Experiment 2, black and white images were used to test whether the green color of plants contributes to PAD. In Experiment 3, all items were rotated by 180° to disrupt semantic recognition and assess whether PAD arises from higher-level cognitive processes. Results revealed a consistent underestimation of plants in Experiment 1 and 2, but this effect diminished in Experiment 3. The reduction of this effect suggests that semantic recognition processes may contribute to PAD. These results highlight how cognitive biases toward plants can influence basic perceptual judgments essential for everyday functioning.